Políticas públicas para a educação básica avanços, desafios e perspectivas - Parente, Cláudia da Mota Darós (Editora Oficina Universitária, 2021)
This book systematizes fundamental analyses, discussions and reflections to understand the current scenario of public policies for basic education in Brazil, highlighting advances, challenges and perspectives in the area.